K-Band Waveguide Resonator Bandpass Filter Structure With Adjustable Transmission Zeros for Producing Various Symmetric and Asymmetric Responses - Sanggu Lee; Jongheun Lee; Boyoung Lee; Jaehwan Lim; Jaesub Han; Juseop Lee (IEEE Access)
This work is to present a versatile K-band waveguide resonator bandpass filter structure capable of producing various responses with a pair of transmission zeros. One of the significant features of the presented filter structure is its ability to produce very dissimilar responses through fine adjustment of tuning screws without changing the geometries of the resonators and coupling structures. The versatility of the filter includes the ability to adjust the proximity of a pair of transmission zeros to the passband. In addition, its asymmetric responses can be laterally inverted by simply changing the resonant frequencies of the resonators without altering the coupling values of the coupling structures. The versatility of the filter can be attributed to the waveguide filter structure using the same type of coupling structures, inductive irises, and avoiding both negative couplings and cross couplings. For filter designs, this work presents a direct synthesis approach to finding the normalized coupling values from a prescribed canonical power transfer function containing a pair of transmission zeros without using numerical methods. One interesting feature is that there is an infinite number of synthesis results corresponding to a predefined response. The filter synthesis approach is demonstrated using examples of third- and fourth-order filters, each featuring a pair of transmission zeros. The versatility of the presented filter is illustrated by a fabricated fourth-order waveguide filter, tuned to produce, for example, three symmetric and four asymmetric responses.